1999
DOI: 10.1111/j.1540-8175.1999.tb00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Detection of Occult Cor Pulmonale During Exercise in Patients with Chronic Obstructive Pulmonary Disease

Abstract: We tested the ability of cycle ergometer exercise echocardiography to detect cases of occult cor pulmonale among 25 patients with chronic obstructive pulmonary disease (COPD). The M-mode echocardiographic ventricular septal motion, left ventricular shape determined by short-axis two-dimensional (2-D) echocardiography, and right and left ventricular pressure curves were recorded at rest and during exercise and were compared between patients. The ventricular septal motion was normal at rest in all of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…We also demonstrated the correlations between SF-36 domains with pulmonary function test results and positive correlations between SF-36 domains with PVO 2 and AT values consistent with the literature (19, 37, 38). However we did not find relationship between PH and quality of life.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We also demonstrated the correlations between SF-36 domains with pulmonary function test results and positive correlations between SF-36 domains with PVO 2 and AT values consistent with the literature (19, 37, 38). However we did not find relationship between PH and quality of life.…”
Section: Discussionsupporting
confidence: 79%
“…Kruger et al (34) have also found negative correlation between serum BNP level with PVO 2 and AT values in 70 patients with congestive heart failure. Eroğlu et al (35) evaluated the relationship between BNP levels and CPET parameters in patients with dyspnea and isolated left ventricle diastolic dysfunction and found negative correlation between BNP levels and duration of exercise, AT VO 2 , and MET on CPET.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…When pulmonary hypertension progresses, the RV dilates in both end-diastolic and end-systolic volumes. Cor pulmonale leads to changes in RV and LV structures or functions caused by pulmonary hypertension associated with the involvement of the lung or its vasculature 2-6)24-26). There are few studies in which cardiac volumes and functions of patient with cor pulmonale are assessed by RT3DE.…”
Section: Discussionmentioning
confidence: 99%